Evaluasi Rasionalitas Penggunaan Antibiotik pada Pasien dengan Infeksi Saluran Kemih di Rumah Sakit X di Surakarta - Adhi Wardhana Amrullah; Avianti Eka Dewi Aditya Purwaningsih; Rolando Rahardjoputro; Atiek Murharyati (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2022)
The study was conducted by evaluating the rationality of antibiotics as an indicator of the rationality of antibiotic administration with the aim of knowing the level of rationality of the pattern of prescribing antibiotics for urinary tract infections The rationality analysis method of prescribing antibiotics in this study used the Gyssens method as a method in medical research used to determine the rationality of antibiotic administration. This research is a descriptive observational study with a cross-sectional method. The data was obtained from a retrospective search of medical records from January to December 2020 at the medical records section of the Hospital in Surakarta. The results showed that the number of patients with urinary tract infections who were hospitalized during 2020 was 104 patients and the number of patients who received antibiotic prescriptions was 80 patients. The results of rationality analysis showed that the antibiotics used in patients with urinary tract infections were 27 (33.75%) cases of antibiotic use including category 0 (zero) which means rational use of antibiotics. Irrational use of antibiotics occurred in category III-A as 40 cases (50%), II-B as 11 cases (13.75%), and the combination of II B with III A as 2 cases (2.5%).